Aspects of corporate governance in the companies bill, 2008- a critical and comparative analysis - Greyling, Nicole (Department of Commercial Law, 2025)
While the role corporate governance should play in a corporation is understood differently from profession to profession and from country to country, its theme has always been to answer this question: in whose interests does a company operate? What we are able to garner from differing opinions is that corporate governance is a concept which is neither irrelevant to the modern corporation nor is it an 'arcane and technical topic' 1. Rather, it is an area of business and the law that has, in only the last decade, been revived and re-debated with renewed interest and enthusiasm. It is acknowledged there is indeed a link between poor corporate governance practices in major corporations and the downturn in an economy, due possibly to the failings of these corporations 2. So too has it been identified that willingness of shareholders to pay a premium for their investments in a corporation is linked to their confidence in good corporate governance structures within that corporation 3. The OECD's Directorate for Financial Enterprise Affairs concludes that '[g]ood corporate governance plays a vital role in underpinning the integrity and efficiency of financial markets.